Retinal Nerve and Vascular Changes in Prediabetes - Peng, Rui Ping; Zhu, Zi Qian; Shen, Hong Yi; Lin, Hong Mei; Zhong, Lei; Song, Si Qi; Liu, Tian; Ling, Shi Qi (Frontiers in Medicine, 2022)
Objective: To observe vascular and neuroretinal alterations in people with prediabetes (impaired fasting glucose(IFG) and impaired glucose tolerance(IGT)) and normal glucose metabolism. Methods: A total of 21 patients with prediabetes (42 eyes) and 20 healthy controls (40 eyes) participated in our study. All patients underwent a complete eye examination (including fundus fluorescein angiography [FFA] and optical coherence tomography [OCT]) and a related general examination (complete biochemical analysis, routine blood tests, glycosylated hemoglobin). Results: On FFA, no patients in either group showed any microvascular alterations. The total peripapillary retinal nerve fiber layer (pRNFL) in the prediabetic group was significantly thinner than that in the healthy control group (p < 0.0001), but only the temporal pRNFL thickness was significantly less in patients with prediabetes compared to the normal people.There was no significant difference in the thickness of retinal nerve fiber layer(RNFL) in the range of 1mm diameter of macular fovea ((p = 0.286), but in the prediabetic group, the macular retinal thickness within the diameter of 6mm in nasal side (p < 0.0001), superior side (p < 0.0001), temporal side (p = 0.008) and inferior side ((p = 0.001) were lower than that in the control group. Conclusion: In the prediabetic group,there was no microvascular alterations, but the total pRNFL and the temporal pRNFL was significantly thinner and the macular retinal thickness within the diameter of 6mm in nasal , temporal and inferior side were lower than that in the healthy control group.These data confirm neuroretinal alterations in prediabetes prior to microvascular injury.